2014
DOI: 10.4194/1303-2712-v14_2_28
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to investigate metabolic adaptation to monthly variations in sea bream reared in Mediterranean off-shore tanks. For this purpose, each month (from October 2010 until June 2011), on 25 Sparus aurata always randomly captured by the same batches in Sicilian farm, fork length, body weight and visceral weight were measured and blood samples were collected. Using biometric data condition factor, viscero-somatic index were calculated and on blood samples biochemical profile was assessed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…Afterward, cortisol was not influenced by any factor, while glucose increased in animals brought from 17 to 23 • C (LH). Our findings on glucose levels are in contrast with cold-induced hyperglycemia observed in studies on gilthead sea bream undertaken in both outdoor and indoor conditions (Rotllant et al, 2001;Faggio et al, 2014;Matias et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Afterward, cortisol was not influenced by any factor, while glucose increased in animals brought from 17 to 23 • C (LH). Our findings on glucose levels are in contrast with cold-induced hyperglycemia observed in studies on gilthead sea bream undertaken in both outdoor and indoor conditions (Rotllant et al, 2001;Faggio et al, 2014;Matias et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…While LDH and AST levels were higher at 17 • C, ALP was very high in animals kept at 23 • C. Then, after the temperature switch, ALP, AST, and LDH were found to be influenced by dietary lipids, with greater levels in response to high dietary lipid diet (L21). In the present study, the elevated blood LDH activity found at low temperatures before temperature changes could probably be caused by lactate accumulation in aerobic tissues such as red muscle and heart indicating an activation of the anaerobic component of metabolism during exposure to cold (Faggio et al, 2014;Feidantsis et al, 2020b). Before temperature switch, TRIG and HDL were more elevated at 17 • C. These results are consistent with increased triglyceride levels found during the colder months, interpreted as a mobilization of the lipid deposits to use as fuels by Faggio et al (2014).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…A severe hypoxia developed with the cessation of breathing in deep anaesthesia which leads to a rise in the partial pressure of blood carbon dioxide, adrenaline concentration, and a fall in blood pH [86]. The haematological parameters were altered when fish were orally administered with gum Arabic showing significant changes in thrombocyte count [87]. The haematological parameters along with micronuclei induction and the pathological marker enzyme activities were greatly altered when C. punctatus were exposed to thermal power plant effluents containing heavy metals like Fe, Cu, Zn, Mn, Ni, Co and Cr [88].…”
Section: Effects Of Oxidative Stress On the Physiology And Metabolic mentioning
confidence: 99%
“…In the aquatic environment, fish is considered as one of the most important indicators of contamination (Aliko, Mehmeti, Qirjo, & Faggio, 2019;Alimba & Faggio, 2019;Faggio et al, 2014a;Faggio et al, 2014b;Fazio, Marafioti, Arfuso, Piccione, & Faggio, 2013). Since fish are at the highest point in the aquatic food chain and have the ability to enlarge the biosensing of heavy metals even at low concentrations in the environment (Bhagwant & Bhikajee, 2000).…”
Section: Introductionmentioning
confidence: 99%